2016
DOI: 10.22487/jimut.v2i1.43
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kinerja Keuangan Pt. PLN (Persero) Indonesia Periode 2011-2015

Abstract: The purpose of the research is to analyze the financial performance and financial health of PT. PLN (Persero) Indonesia in 2011- 2015 based on the Decree of the Ministry of State-Owned Enterprises No: KEP-100/MBU/2002 on company’s health assessment on eight indicators: ROE, ROI, Current Ratio, Cash Ratio, Collection Period, Inventories, Total Assets Turn Over, and Total Ratio of Own Capital to Total Assets and Trend Analysis. The result shows that the financial performance of the liquidity ratio indicates that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Concerning the mentioned considerations, the research discusses the financial performance of PT PLN (Persero). Previously, several researchers, such as Lafera (2020), Utari (2020), Rahmawati (2019), Sari (2018), andSari, Husnah, andFattah (2016), have conducted quantitative-descriptive research mainly through ratio analysis to explain the financial performance of PT PLN (Persero). Moreover, the results are varied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the mentioned considerations, the research discusses the financial performance of PT PLN (Persero). Previously, several researchers, such as Lafera (2020), Utari (2020), Rahmawati (2019), Sari (2018), andSari, Husnah, andFattah (2016), have conducted quantitative-descriptive research mainly through ratio analysis to explain the financial performance of PT PLN (Persero). Moreover, the results are varied.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the results are varied. In the research by using the period time before 2018 (2013−2017, 2010−2017, 2011−2015), the researchers have found that the financial performance of PT PLN (Persero) is considered poor (Sari, Husnah, & Fattah, 2016;Sari, 2018;Rahmawati, 2019). Meanwhile, under the time frame of 2018 and above (2017−2018, 2016−2018, 2018−2022), the researchers have suggested that the financial performance of PT PLN (Persero) improves (Lafera, 2020;Utari, 2020;Rahmawati, 2019).…”
Section: Introductionmentioning
confidence: 99%